One pot synthesized Li, Zr doped porous silica nanoparticle for low temperature CO2 adsorption - Mani Ganesh; Pushparaj Hemalatha; Mei Mei Peng; Hyun Tae Jang (Arabian Journal of Chemistry, 2017)
Li, Zr doped porous silica was synthesized in one pot and investigated for low temperature CO2 adsorption. The synthesized nanoparticle was characterized by X-ray diffraction (XRD), N2 adsorption–desorption measurement, thermogravimetric analysis (TGA) and scanning electron microscopy (SEM). The specific surface area, average pore diameter and pore volume were determined to be 962 m2/g, 2.3 nm and 0.56 cm3/g respectively. ICP-AES analysis revealed a metal content of 4 wt.% (Zr) and 3.42 wt.% (Li). Their CO2 adsorption capacity was tested at room temperature and atmospheric pressure. An uptake of about 5 wt.% was observed and regenerable at a low temperature of 200 °C. This adsorption and desorption temperature of the sorbent is lower than the reported lithium silicate. The CO2 adsorption–desorption cyclic performance studies illustrated that Li, Zr doped porous silica is a recyclable, selective and potential sorbent for CO2 adsorption.